2022
DOI: 10.1513/annalsats.202103-340oc
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Health Problems beyond Pulmonary Recovery up to 6 Months after Hospitalization for COVID-19: A Longitudinal Study of Respiratory, Physical, and Psychological Outcomes

Abstract: Rationale: Data on longitudinal recovery after hospitalization for SARS-CoV-2 remain currently scarce, just as outcomes beyond 3 months follow-up. Objective:The aim of the study was to evaluate the sequelae up to 6 months after hospitalization for SARS-CoV-2 infection, considering 1) the recovery of pulmonary function and radiological abnormalities, physical and mental health status, and health-related quality of life (HR-QoL); and 2) the predictors of the most clinically relevant sequelae. Methods:Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 41 publications
3
41
0
Order By: Relevance
“…Whether PTSD is also highly prevalent in the aftermath of different COVID-19 populations remains to be determined. Previous published studies reported prevalences of symptoms of PTSD ranging from 10% to 30% in patients discharged from the hospital [5][6][7][8][9][10][11][12], which is lower than the current prevalence rates from hospitalized as well as nonhospitalized patients.…”
Section: Comparison With Prior Studiesmentioning
confidence: 57%
See 3 more Smart Citations
“…Whether PTSD is also highly prevalent in the aftermath of different COVID-19 populations remains to be determined. Previous published studies reported prevalences of symptoms of PTSD ranging from 10% to 30% in patients discharged from the hospital [5][6][7][8][9][10][11][12], which is lower than the current prevalence rates from hospitalized as well as nonhospitalized patients.…”
Section: Comparison With Prior Studiesmentioning
confidence: 57%
“…Accordingly, COVID-19 might also lead to PTSD. Indeed, previous studies reported prevalences of symptoms of PTSD ranging from 10% to 30% in patients discharged from the hospital [5][6][7][8][9][10][11][12]. Prevalences of symptoms of anxiety and depression in these samples vary between 5% and 42% [7,[9][10][11][12] and 14% and 31% [6,9,11,12], respectively.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…With more recent studies and longer-term follow-up data, however, it becomes increasingly clear that although pulmonary function impairment is common after hospitalisation for COVID-19, this gradually recovers towards normal values up to 1 year after discharge [ 9 , 10 ]. Likewise, radiological abnormalities gradually improve over time and are rarely severe [ 11 ].…”
mentioning
confidence: 99%